The Effect of Reaction Time and Temperature on the Synthesis of Methyl Ester Sulfonate Surfactant from Palm Oil as a Feedstock using Microwave-Assisted Heating - Lailatul Qadariyah; Sahiba Sahila; Mahfud Mahfud (ASEAN Journal of Chemical Engineering, 2021)
Methyl ester sulfonate is an anionic surfactant that can be synthesized from palm oil as a raw material with the addition of sodium bisulfite and calcium oxide catalyst through transesterification and sulfonation process using microwave-assisted heating. The effect of microwave-assisted heating in the transesterification-sulfonation process was investigated in this study. The transesterification process was carried out using a microwave power of 300 watts for 10 minutes with an addition of a KOH catalyst of 1%. The transesterification process gave a result of palm oil methyl ester with a yield of up to 98% and density of 0.8546 gr/ml, and kinematic viscosity of 3.19 cSt. The sulfonation process is carried out using palm oil methyl ester and sodium bisulfite with a mole ratio of 1:3 and calcium oxide catalyst of 1.5% with the microwave power of 300 watts while varying the sulfonation time and temperature. The physicochemical properties of methyl ester sulfonate were analyzed, and the sulfonate group was characterized using FTIR. The optimum condition gave a yield of up to 98.68%, the density of 0.8657 gr/ml, viscosity of 3.75 cSt, pH of 2.12, and surface tension of up to 27.34 dyne/cm at a temperature of 100oC and sulfonation time of 40 minutes.